Case Report: Modified Thoracoscopic-Assisted Cervical Resection for Retrosternal Goiter - Nesti, Cédric; Wohlfarth, Benny; Borbély, Yves M.; Kaderli, Reto M. (Frontiers in Surgery, 2021)
Introduction: The treatment of choice for retrosternal goiters (RSG) is surgical resection to relieve symptoms and rule out malignancy. Although the majority of RSG can be removed by a cervical approach only, an extracervical approach (e.g., sternotomy, thoracotomy or thoracoscopy) may be required. Herein, we describe a refined thoracoscopic-assisted cervical two-team RSG resection without thoracoscopic mediastinal dissection. Technique: A 57-year-old man presented with a large RSG with posterior mediastinal extension (PME) and extensive peritumoral vascularization. Due to its extension below the aortic arch and its small connection with the right thyroid lobe, a combined cervical and thoracoscopic approach was intended. The endocrine surgery unit performed the cervical mobilization of the right thyroid lobe, while the thoracic surgery unit gently pushed the mediastinal tumor through the thoracic inlet without performing mediastinal dissection. This allowed a safe visualization of the inserting vessels by the endocrine surgery team at the neck, followed by a stepwise division of the vessels and resection of the retrosternal nodule through the cervical access. Comment: The described approach is indicated for RSG with posterior mediastinal extension, anteroposterior dimension smaller than the thoracic inlet and inaccessibility from a cervical approach only. This minimally invasive approach is associated with a faster recovery, decreased morbidity and postoperative pain, shorter hospital stay and better cosmetic results.